Exploring the Relationship Among Divergence Time and Coding and Non-coding Elements in the Shaping of Fungal Mitochondrial Genomes - Fonseca, Paula L. C.; Badotti, Fernanda; De-Paula, Ruth B.; Araújo, Daniel S.; Bortolini, Dener E.; Del-Bem, Luiz-Eduardo; Azevedo, Vasco A.; Brenig, Bertram; Aguiar, Eric R. G. R.; Góes-Neto, Aristóteles (Frontiers in Microbiology, 2020)
The order Hypocreales (Ascomycota) is composed of ubiquitous and ecologically diverse fungi such as saprobes, biotrophs, and pathogens. Despite their phylogenetic relationship, these species exhibit high variability in biomolecules production, lifestyle, and fitness. The mitochondria play an important role in the fungal biology, providing energy to the cells and regulating diverse processes, such as immune response. Although its importance, the mechanisms that shape fungal mitogenomes are still poorly understood. Herein, we investigated the variability and evolution of mitogenomes and its relationship with the divergence time using the order Hypocreales as a study model. We sequenced and annotated for the first time Trichoderma harzianum mitochondrial genome (mtDNA), which was compared to other 34 mtDNAs species that were publicly available. Comparative analysis revealed a substantial structural and size variation on non-coding mtDNA regions, despite the conservation of copy number, length, and structure of protein-coding elements. Interestingly, we observed a highly significant correlation between mitogenome length, and the number and size of non-coding sequences in mitochondrial genome. Among the non-coding elements, group I and II introns and homing endonucleases genes (HEGs) were the main contributors to discrepancies in mitogenomes structure and length. Several intronic sequences displayed sequence similarity among species, and some of them conserved even at gene position, and were present in the majority of mitogenomes, indicating its origin in a common ancestor. On the other hand, we also identified species-specific introns that advocate for the origin by different mechanisms. Investigation of mitochondrial gene transfer to the nuclear genome revealed that nuclear copies of the nad5 are the most frequent while atp8, atp9, and cox3 could not be identified in any of the nuclear genomes analyzed. Moreover, we also estimated the divergence time of each species and investigated its relationship with coding and non-coding elements as well as with the length of mitogenomes. Altogether, our results demonstrated that introns and HEGs are key elements on mitogenome shaping and its presence on fast-evolving mtDNAs could be mostly explained by its divergence time, although the intron sharing profile suggests the involvement of other mechanisms on the mitochondrial genome evolution, such as horizontal transference.